Injury Characteristics Among Pediatric Athletes Who did and did not Undergo a CT Scan Following Concussion. Issue 5 (31st May 2022) - Worrall, Hannah M.; Miller, Shane M.; Chung, Jane S.; Stokes, Mathew A.; Tow, Stephanie; Cullum, C. Munro; Jones, Jacob C.
Background: CDC and AAP guidelines discourage routine neuroimaging following concussion, as CT scans are only indicated if severe intracranial injury is suspected. Validated prediction rules such as Pediatric Emergency Care Applied Research Network (PECARN) criteria have decreased the number of unnecessary pediatric head CTs; however, are still commonly performed following pediatric sport-related concussion (SRC). Hypothesis/Purpose: To determine differences in injury characteristics and outcomes in athletes who did and did not undergo head CT following SRC. Methods: Data were prospectively collected from participants enrolled in the North Texas Concussion Network Registry (ConTex) between August 2015-May 2021. Participants aged 5-18 diagnosed with SRC and presenting within 30 days were included. Participants were separated into 2 groups based on whether they had a CT scan following SRC: CT (negative scan) and no CT. Positive CTs were excluded. Groups were matched in age and time to presentation (≤14, >14-30 days). Demographics, concussion-related details, and 3-month outcome variables were analyzed including days to symptom resolution (≤30 vs >30 days) and return-to-play (RTP). Results: 324 participants were included: 162 in each group. There were no significant differences between the groups in sex, race, ethnicity, or previous concussion history. Differences in injury-related characteristics are reported in Table 1. Participants in the CT group were more likely to be participating in unorganized events (p=0.05), and less likely to continue playing following SRC (p=0.003) than the no CT group. The CT group more frequently reported head to surface mechanism of injury than the no CT group. Significantly higher rates of loss of consciousness (LOC), amnesia, and vomiting following SRC were reported in the CT group. At 3-months post-SRC, the no CT group reported RTP a week sooner than the CT group (28.8±22.3 vs 35.7±27.3 days, p=0.019). However, there was no difference in prolonged recovery (>30 days: 29.6 vs 40.5%, p=0.07) or overall RTP rates (91.9 vs 85.8%, p=0.09) between the no CT and CT groups. Conclusion: Pediatric athletes who underwent CT following SRC exhibited significantly different injury-related characteristics compared to those who did not, but the differences observed did not impact symptom resolution or return-to-play. While LOC and vomiting differences align with the PECARN prediction rules and likely contribute to decision to perform CT, the additional differences of participating in an unorganized event, head-to-surface impact, and amnesia are not part of PECARN criteria. Further research is needed to discover which variables may contribute to unnecessary head CTs following SRC. Table 1. Injury related characteristics between the CT and no CT scan groups